2016
DOI: 10.1051/swsc/2016029
|View full text |Cite
|
Sign up to set email alerts
|

High-latitude ion temperature climatology during the International Polar Year 2007–2008

Abstract: This article presents the results of an ion temperature climatology study that examined ionospheric measurements from the European Incoherent SCATter ( -2012). Fairly close agreement was found between the observations and TIE-GCM results. Numerical experiments revealed that the daily variation in the high-latitude ion temperature, about 100-200 K, is mainly due to ion frictional heating. The ion temperature was found to increase in response to elevated geomagnetic activity at both ESR and PFISR, which is cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 54 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Yamazaki et al. (2016) used ESR data from the solar minimum years 2007–2008 and found a pattern of ion temperature variations that is, similar to the pattern shown in Figure 6. Using TIE‐GCM model simulations, they showed that the observed ion temperature enhancements are mainly caused by ion frictional heating.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Yamazaki et al. (2016) used ESR data from the solar minimum years 2007–2008 and found a pattern of ion temperature variations that is, similar to the pattern shown in Figure 6. Using TIE‐GCM model simulations, they showed that the observed ion temperature enhancements are mainly caused by ion frictional heating.…”
Section: Discussionmentioning
confidence: 62%
“…This might suggest that the formation of the depletion region observed in the ESR data is connected to frictional heating Vanhamäki et al (2016). andVoiculescu et al (2016) observe an increase in the ion temperature colocated with a high-latitude post-midnight trough, and they suggest that ion frictional heating might play a part in the formation of the observed trough Yamazaki et al (2016). used ESR data from the…”
mentioning
confidence: 99%
“…AE index has previously been assessed as a driver index of F region ionospheric storm variability in the works of Wu and Wilkinson () and Perrone et al (), demonstrating comparable performance to other common geomagnetic indices, such as Dst and Ap . At high latitudes, with the dominant ionospheric storm time response being driven by Joule heating in the vicinity of the auroral electrojets (Yamazaki et al, ), AE , as an auroral electrojet index, acts as a convenient proxy of this heating. For a potential global reparameterization of the NeQuick, other indices may be necessary to reflect the different physical processes governing the ionospheric response to storms in different regions of the globe.…”
Section: A Refitted and Parameterized Nequick Topsidementioning
confidence: 99%